Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/acn3.261
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of agrin‐22 production and synaptic dysfunction in Cln1−/− mice

Abstract: ObjectiveOxidative stress in the brain is highly prevalent in many neurodegenerative disorders including lysosomal storage disorders, in which neurodegeneration is a devastating manifestation. Despite intense studies, a precise mechanism linking oxidative stress to neuropathology in specific neurodegenerative diseases remains largely unclear.MethodsInfantile neuronal ceroid lipofuscinosis (INCL) is a devastating neurodegenerative lysosomal storage disease caused by mutations in the ceroid lipofuscinosis neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Recent studies indicate that Serpina1 is associated with various diseases, such as sporadic amyotrophic lateral sclerosis, cancers, schizophrenia, bipolar disorder, and frontotemporal dementia [ 24 , 25 , 26 , 27 ]. Furthermore, a recent study by Peng et al indicated that up-regulation of Serpina1 could suppress agrin-22 production and eventually lead to synaptic dysfunction [ 28 ]. In the present study, the significantly down-regulated Serpina1 may play an important role in maintaining axonal stabilization post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Serpina1 is associated with various diseases, such as sporadic amyotrophic lateral sclerosis, cancers, schizophrenia, bipolar disorder, and frontotemporal dementia [ 24 , 25 , 26 , 27 ]. Furthermore, a recent study by Peng et al indicated that up-regulation of Serpina1 could suppress agrin-22 production and eventually lead to synaptic dysfunction [ 28 ]. In the present study, the significantly down-regulated Serpina1 may play an important role in maintaining axonal stabilization post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this experimental setting, an increased expression of a wild-type CLN1 was functionally linked to DEGs encoding palmitoylated neuronal proteins, pinpointed impaired cellular functions (i.e., neuritogenesis) and coupled with dysregulated expression of synapse-related genes. Affected modules and related functions are associated with the pathological effects related to loss-of-function, and are known to be affected in Ppt1 −/− mice, including pathological changes of a synaptic compartment (Virmani et al, 2005 ; Kielar et al, 2009 ; Peng et al, 2015 ; Tikka et al, 2016 ); moreover a severe epilepsy associated with typical Electroencephalogram (EEG) pattern (Santavuori, 1973 ) occurs in CLN1 patients, who are lacking PPT1 functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence for the potential role of neurotrypsin in synaptic homeostasis comes from a recent study in which it was postulated that synaptic dysfunction found in Cln1−/− mice, a mouse model of infantile neuronal ceroid lipofuscinosis (INCL), could be due to, at least in part, a novel mechanism that links oxidative stress with suppression of agrin 22 production in INCL disease. Interestingly, they showed that treatment with a specific antioxidant, NtBuHA, elevated agrin 22 levels, and therefore, may have therapeutic implications for this devastating disease (Peng et al, 2015 ).…”
Section: Activity-dependent Ecm Remodelingmentioning
confidence: 99%